Patterns of growth and change among the Mandaya of Montevista - Cruz, Amihan D.
Hitherto, researchers and anthropologists have done varying studies in an attempt to explore the Mandaya indigenous group. Their studies had been successful. As we can see in the Filipiniana section of our libraries and in some of our government offices today, books and write-ups about this indigenous group abound. The Patterns of Growth and Change Among the Mandaya of Montevista is an in-depth examination of how this separate assembly from the same indigenous group mai8ntains and expresses the dynamism of their culture, and how Bisaya (non- natives) brought them to their current trend of lifestyle. Aside from containing the patterns of growth and change in the structure of the Mandaya of Montevistas' culture, the contents also include their current thought and information about the development and alterations occurring. The patterns of growth and change that the Mandayas has undergone, gradually diminished their traditional culture. Basically, education is the institution that triggered the changes in the other social components. Religion on the other hand, is the tool that the Bisaya (non- natives) used to initiate the initial interaction with the Mandaya. The Mandaya community of Montevista, Davao del Norte has been chosen as the target population, because a study has not been conducted yet in this band of Mandaya which is a pre- requisite posted by the Center for Integrative and Development Studies (CIDS).